LC–MS-Based Lipidomic Analysis of Serum Samples from Spontaneously Hypertensive Rats Treated with an Extract of Acanthopanax sessiliflorus Fruits - Dae Young Lee; Bo-Ram Choi; Dahye Yoon; Hyoung-Geun Kim; Min-Ho Lee; Geum-Soog Kim; Young-Seob Lee (Molecules, 2020)
Recently, lipidomics has revealed that many diseases are highly associated with altered lipid metabolism, as in the case of hypertension affecting serum lipid metabolism. In this study, an LC–MS-based lipidomic approach was used to profile serum lipids in spontaneously hypertensive rats (SHRs) treated with an extract of Acanthopanax sessiliflorus fruits (ASF), to elucidate the serum lipid metabolism alteration by hypertension and the treatment of a drug or ASF. First, UPLC-QTOF/MS profiled a total of 208 lipids from six pooled samples of normal controls, SHR, SHR + 100 mg/kg of drug, and SHR + ASF 200, 400, or 600 mg/kg. These six groups were differentiated by the PCA and sPLS–DA, and 120 lipid species were identified as differentially regulated lipids (DRLs) by ANOVA (p values < 0.05). Second, UPLC–QqQ/MS was used for the target profiling of 120 DRLs from individual samples of the six groups. Using an ANOVA, 67 lipids (38 TGs, 4 DGs, 17 PCs, 2 PEs, and 6 LPCs) were selected as validated DRLs. The mostly altered lipids, such as TG (62:13), TG (60:13), PC (34:4), PC (36:5), and PC (38:2), were decreased in SHR compared to the normal control, and received little by treatment with ASF. These results demonstrated the correlation between hypertension and serum lipid metabolism. Furthermore, both drug and ASF treatment similarly altered the lipid profiles of SHRs. Finally, we found that DRLs have the potential to help us to interpret the lipid metabolism of hypertension.